MORAL ATTITUDE OF FUTURE FOREIGN LANGUAGE TEACHERS: COGNITIVE – MEANINGFUL LEVEL - Kriaučiūnienė, Roma (Acta Paedagogica Vilnensia, 2008)
Lithuanian and foreign researchers acknowledge the fact that that there is no education without values and that it is the teacher‘s responsibility to transmit those values to students. Lithuanian laws and regulations on education as well as Eureopean Centre for Modern Languages also see the need generated by present times to develop within our students the skills, values and behaviours of learning to live together. Therefore, the article raises the question wether universities pay enough attention to the development of moral attitudes of future foreign language teachers so that they can proceed with the fulfilment of their responsibility – teaching values and attitudes that help students connect international, national and personal dimensions with respect to linguistic and cultural diversity. The theoretical background of the reseach into moral attitudes of future foreign language teachers is provided in the article and it is based on the analysis of psychological, philosophical and pedagogical literature. Three models of attitude structure are overviewed. Philosophers maintain that moral attitudes manifest themselves by moral evaluative judgements. They also stress the fact that moral values are the criteria for making moral judgements concerning oneself, other people, phenomena, or things. Pedagogical literature revealed the importance of moral values in an individual value system. Such moral values as respect, honesty, sincerity, truthfullness, responsibility etc. determine the nature of moral attitudes, direct one‘s behaviour and provide the basis for human relationships. Therefore, the acknowledgment of the importance and understanding of the meaningfulness of moral values are considered to be the criteria revealing the depth and maturity of the cognitive-meaningful component of one‘s moral attitudes. The reseach into moral attitudes of future foreign language teachers was conducted at Vilnius Pedagogical Universities. The article provides the results of the analysis of the cognitive–meaningful component of foreign language students‘ moral attitudes. Although the respondents showed a relatively high acknowledgment of the importance of moral values, the understanding of meaningfulness of these moral values is not very deep. The conclusion is made that such a level of cognitive- meaningful level of moral attitudes of future foreign language teachers is not mature enough and that it might hinder the fulfilment of teachers‘ responsibilities in their future professional areas.